Afatinib for the treatment of advanced non-small-cell lung cancer. (April 2014) - Genova, Carlo; Rijavec, Erika; Barletta, Giulia; Burrafato, Giovanni; Biello, Federica; Dal Bello, Maria Giovanna; Coco, Simona; Truini, Anna; Alama, Angela; Boccardo, Francesco; Grossi, Francesco
<x xml:space="preserve">Abstract</x> Introduction: The inhibition of the epidermal growth factor receptor (EGFR) through tyrosine kinase inhibitors (TKIs) represents an effective strategy for EGFR-mutated NSCLC. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Afatinib&logicalOpe1=OR&field2=articletitle&text2=Afatinib&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Afatinib is an irreversible erythroblastosis oncogene B (ErbB) family blocker, able to inhibit the kinase domains of EGFR, HER2 and HER4, and the transphosphorylation of ErbB3 that has recently been approved in the United States for the first-line treatment of EGFR-mutated NSCLC and in Europe and Japan for the treatment of EGFR-mutated TKI-naive patients. Areas covered: The authors analyzed the pharmacology and the clinical activity of afatinib in NSCLC through a review of the literature. Trials exploring different settings have been reported, including LUX-Lung 3 and LUX-Lung 6, where the drug achieved better outcomes in terms of response rate, progression-free survival and quality of life compared with chemotherapy. The main toxicities of afatinib are gastrointestinal and skin-related adverse events. Expert opinion: Afatinib showed remarkable efficacy as a first-line treatment in the presence of common EGFR mutations. Afatinib showed some activity in NSCLC with acquired resistance to EGFR TKIs, although, currently, its efficacy after the failure of erlotinib or gefitinib has not been clearly stated. Direct clinical data comparing the activity and tolerability of different inhibitors are still needed.